Um estudo baseado em dissertações e teses sobre sexualidade em programas de pós-graduação em educação em Minas Gerais (1997-2014) - Souza, Juliane Cristina Ribeiro Borges de (2018)
This research is a descriptive and analytical study of academic production on sexuality, about dissertations and theses produced in postgraduate programs in Education in the state of Minas Gerais, between 1997 and 2014. The research consisted in qualitative and quantitative character and bibliographical nature, with characteristics and resources of a study of the State of Art and was structured in two complementary stages. The first stage was composed of the quantitative survey of dissertations and theses and, in the second stage, an analytical study based on descriptors, mainly with emphasis on the levels of teaching, thematic focuses and problems investigated in dissertations and theses.The research at this stage was based on studies in the fields of sexuality, gender and education. It was identified 47 dissertations and theses, developed predominantly in institutions of public nature (95.8%) among which UFMG, UFU and UFJF stand out, which together account for 74.6% of inventoried production. There is a clear predominance in the production of master's dissertations, accounting for 76.6% of the works. Among the 27 studies that were applied with students, the distribution of most of them in Elementary School 2 (6th to 9th grade) (33.3%) being Infantile Education, Primary Education 1 (1st to 5th year) and Education for Young People and Adults, underprivileged levels in the analyzed works. The two thematic focuses with the greatest number of approaches are "Gender Studies" and "Professional Look", representing 65.9% of the production investigated. Thematic focuses that were less expressive were "Sexuality and special needs" (2 approaches) and "Bibliographic review studies" (2 approaches), only as a secondary focus. As a result of this research, an Analytical-Descriptive Catalog of the dissertations and theses analyzed was elaborated.